The Development of Writing Teaching Material Model With Local Wisdom Contents By Using CEFR Standard in English Literature Study Programme - Kusuma, Dwi Linda; Lililacs , Admin (Lililacs Journal, 2022)
The theme of local wisdom is an example of an interesting theme in writing activities and could be developed into a work that contributes to the creative industry and teach cultural values and national identity. In language learning, writing is one of the important skills in reconstructing grammar, vocabulary, and supporting the use of spoken language. Currently, writing skills can also be measured using global measurement standards. The standard is the CEFR (Common European Framework of Reference) which has been used in the European Region. Likewise, the English Literature study program at the State University of Jakarta also teaches writing skills or other skills with CEFR standards. However, in teaching Writing course, lecturers use various references or sources for learning. This means that there are no teaching materials arranged in the form of modules or textbooks as the main reference. Therefore, this research was designed in a research and development scheme to compile teaching materials which contains local wisdom.